2015
DOI: 10.1097/md.0000000000002231
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure is Associated With Cerebral Blood Flow Alterations in Patients With T2DM as Revealed by Perfusion Functional MRI

Abstract: Type 2 diabetes mellitus (T2DM) and hypertension are both associated with cognitive impairment and brain function abnormalities. We investigated whether abnormal cerebral blood flow (CBF) patterns exists in T2DM patients and possible relationships between aberrant CBF and cognitive performance. Furthermore, we examined the influence of hypertension on CBF alterations in T2DM patients.T2DM patients (n = 38) and non-T2DM subjects (n = 40) were recruited from clinics, hospitals, and normal community health screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 37 publications
(42 reference statements)
3
38
0
2
Order By: Relevance
“…This is consistent with our previous findings that T2DM reduces CBF velocity and regional cerebral vasoreactivity of CO 2 challenges in the parietal and occipital regions (Novak et al 2006). Our findings are consistent with a recent T2DM ASL-CBF study (Xia et al 2015). They reported that the main effects of T2DM were primarily in visual and DMN regions.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is consistent with our previous findings that T2DM reduces CBF velocity and regional cerebral vasoreactivity of CO 2 challenges in the parietal and occipital regions (Novak et al 2006). Our findings are consistent with a recent T2DM ASL-CBF study (Xia et al 2015). They reported that the main effects of T2DM were primarily in visual and DMN regions.…”
Section: Discussionsupporting
confidence: 94%
“…The results did not reach an agreement yet. Some studies have reported decreased CBF in T2DM (Xia et al 2015; Novak et al 2006; Last et al 2007; Nagamachi et al 1994), while others did not observe CBF alteration in T2DM (Tiehuis et al 2008; Rusinek et al 2015; Novak et al 2011). Most of the studies reporting no CBF alteration in T2DM typically used large regions of interest (ROI) and/or did not adequately account for the potential risk factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ele baseia-se nos resultados do estudo de Framingham conduzido predominantemente entre a população caucasiana (Herath, Weerarathna e Umesh, 2015). Entre os principais fatores e hábitos que podem auxiliar no controle da doença estão a alimentação adequada e o controle do peso, que podem proporcionar melhoria no controle glicêmico, com consequente redução de riscos para doenças cardiovasculares e melhora da qualidade de vida (Cecílio, 2015 (Xia, 2015).…”
Section: Resultsunclassified
“…Thus far, some studies, one using phase contrast MRI (1.5T) (Tiehuis et al, 2008) and one using ASL (3T) (Rusinek et al, 2015), did not find any differences in global perfusion between patients with type 2 diabetes and controls, while other studies (ASL, Novak et al, 2014; Xia et al, 2015a and IVIM, van Bussel et al, 2015, all at 3T) observed regional differences in perfusion. Possibly, differences in MRI methodology could explain these conflicting results.…”
Section: Impaired Cerebral Perfusionmentioning
confidence: 99%